Pengaruh Ketidakpastian Tarif Impor dan Kurs Dolar AS Terhadap Potensi Ekspor Produk Halal Bagi UMKM Syariah - Arifa Pratami; Yesi Safitri; Wahdinil Jannah; Riki Gunawan (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the impact of import tariff uncertainty and US Dollar exchange rate fluctuations on the halal export potential of Islamic MSMEs in Indonesia. In a rapidly changing global economic landscape, Islamic MSMEs are particularly vulnerable to external pressures that can affect their competitiveness in international markets. Using a quantitative approach, data were collected through surveys involving 70 Islamic MSME actors in Medan City and analyzed using multiple linear regression with SPSS 25. The findings reveal that both import tariff uncertainty and exchange rate fluctuations have a significant influence, both partially and simultaneously, on the potential for halal exports. The regression model shows a coefficient of determination of 82.8%, indicating that the two independent variables explain a substantial portion of the variation in export potential. These results provide strategic insights for strengthening the resilience and global competitiveness of Islamic MSMEs amid ongoing economic uncertainty.